Pojęcie nadmiernego przekroczenia terminu na wniesienia odwołania od decyzji organu rentowego do sądu powszechnego - Helmin, Maciej (PRAWO i WIĘŹ, 2025)
The paper is devoted to an examination of the notion of excessive delay in the lodging of an appeal against an administrative decision within the framework of social security proceedings. The author undertakes a critical analysis of the interpretative approaches adopted by the courts in construing this concept and seeks to formulate operational criteria for assessing the extent of delay that may be deemed acceptable on the part of an appellant contesting the impugned decision.